Republic of Indonesia Financial Sector Assessment Program : CPSS Core Principles for Systemically Important Payment Systems - International Monetary Fund; World Bank (Washington, DC, 2017)
This assessment forms part of the joint International Monetary Fund (IMF) and World Bank Indonesia Financial Sector Assessment Program (FSAP) which is being undertaken during 2009-2010. The assessment which covers the Bank Indonesia's real time gross settlement (BI-RTGS) system's observance of the Committee on Payment and Settlement Systems (CPSS) Core Principles for Systemically Important Payment Systems (SIPS) and the Central Bank's Responsibilities in applying the Core Principles was conducted during the first mission. The assessment which was conducted with the cooperation of the Bank Indonesia and other key players in the payment systems area was undertaken by Alice Zanza, Senior Payment Systems Specialist, World Bank with the assistance of Bruce Summers, Senior Payment Systems Advisor, World Bank. Although there are several systems in operation in Indonesia, BI considers the Bank Indonesia Real Time Gross Settlement (BI-RTGS) system to be the only systemically important payment system in the country. BI-RTGS is owned by BI and operated by the Payment Systems Department in the Directorate of Accounting and Payment Systems. To date, the assessment team does not have any information to expand the scope of systemically important payment systems in Indonesia and has conducted the assessment of the RTGS system, as the sole SIPS in the country.